PERAN TEKNOLOGI DIGITAL DAN INSTAGRAM DALAM PROMOSI PAKET UMRAH DI WILAYAH KABUPATEN TASIKMALAYA - Muis Muhammad IS; Hasan Basri; Fakhrija Muhammad Haikal (ARMUZNA : Jurnal Manajemen Haji dan Umrah (MHU), 2024)
Increasingly, the way payments are made through the role of digital technology is growing, the majority of people, especially people who live in urban areas, have already carried out shopping or payment activities through the intermediary of a digital platform. Travel and Umrah providers in Tasikmalaya district are not wasting this good momentum to develop their fundraising and of course can provide maximum service even if only through digital technology. Tasikmalaya district travel and Umrah provider is one of the Umrah package providers who has utilized the role of digital technology as a place for Umrah and Hajj registration and uses it as a marketing place through strategic digital platforms such as marketing through social media websites and others. This research aims to find out about the role of Digital Technology and Instagram in Fundraising for travel and Umrah providers in Tasikmalaya Regency, fundraising strategies for travel and Umrah providers in Tasikmalaya Regency and the Role of Digital Technology and Instagram in Fundraising for Umrah and Hajj rituals in travel and Umrah providers in Tasikmalaya Regency. In this research, researchers used a qualitative approach using data collection techniques, namely direct interviews with travel and Umrah providers in Tasikmalaya Regency and collecting information in the form of data. The results of this research show that travel and Umrah providers in Tasikmalaya Regency apply various types of marketing through digital technology and create content that is interesting and easy to understand by potential donors, such as promoting and creating interesting programs, besides that digital technology can increase the growth of fundraising from travel and Umrah providers in Tasikmalaya Regency. Increasingly, travel and Umrah providers in Tasikmalaya Regency are continuing to develop digital technology.